Testing Reinecke’s chronology of the Early Bronze Age with radiocarbon dating – New evidence from Southern Bavaria - Ken Massy; Philipp W. Stockhammer (Studia Hercynia, 2019)
In this article we present a critical view of the current chronological framework for Early Bronze Age burials from Southern Bavaria, by using radiocarbon dating to re examine Paul Reinecke’s relative chronological classification system. We also examine chronological divisions established by other scholars based on his system. The results of our study show a complex pattern of local groups appropriating new types or styles of objects from others, which then influences the timeline for the appearance of such type objects. Our findings show that every region had its own socio cultural history with a slightly different chronology.